2010
DOI: 10.1099/vir.0.022210-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of U2OS and Huh-7 cells for identifying host factors that affect hepatitis C virus RNA replication

Abstract: Host cell factors are critical to all stages of the hepatitis C virus (HCV) life cycle. While many cellular proteins that regulate HCV genome synthesis have been identified, the mechanisms engaged in this process are incompletely understood. To identify novel cellular proteins involved in HCV RNA replication, we screened a library of small interfering RNAs (siRNAs) targeting 299 cellular factors, which principally function in RNA interactions. For the screen, a robust system was established using two cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 44 publications
6
20
0
Order By: Relevance
“…Previous efforts to investigate how Xrn1 influences HCV replication have produced conflicting results, with two studies showing no effects of Xrn1 depletion (26,27). Our results are consistent with those of Jones et al (28) and Ruggieri et al (29) and provide a mechanism for why Xrn1 depletion promotes HCV replication.…”
Section: Resultssupporting
confidence: 87%
“…Previous efforts to investigate how Xrn1 influences HCV replication have produced conflicting results, with two studies showing no effects of Xrn1 depletion (26,27). Our results are consistent with those of Jones et al (28) and Ruggieri et al (29) and provide a mechanism for why Xrn1 depletion promotes HCV replication.…”
Section: Resultssupporting
confidence: 87%
“…More recently, researchers have been exploring whether the effect of miR-122 on viral translation is merely a stabilization of the viral RNA (8,11,18,32,43). In particular, Xrn1 has been implicated as the major host factor destabilizing and degrading the viral RNA (17,18,29,32), although not all screens involving Xrn1 knockdown show that it has a negative or any effect on HCV (17,(44)(45)(46). Our evidence (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…miR-122 has been observed to modestly increase translation of the viral RNA, but this has recently been attributed to simply increased stability of the viral RNA in the assays, allowing more viral RNA to be translated (10,11,14,15). In particular, miR-122 has been implicated in protecting the 5= end of the viral RNA from degradation by Xrn1, the major cytoplasmic 5=-to-3= exoribonuclease that normally functions to degrade decapped host mRNAs and other Flavivirus RNAs (16)(17)(18)(19). One model posits that the interaction of miR-122 with S1 generates a 3= overhang that shields the 5= triphosphate genome terminus, but the influence of each miR-122 binding interaction in protection from Xrn1 remains unknown.…”
mentioning
confidence: 99%
“…Another protective role of miR-122's interaction with the 5′ terminus of the HCV genome could involve protection from 5′ exonucleases. Depletion of XRN-1 mRNA, encoding a 5′-3′ exonuclease that is involved in decay of cellular mRNAs (24,25), increases the expression of luciferase from tricistronic HCV replicons (26) and the abundance of electroporated HCV replicon RNA. Interestingly, Takahashi et al reported that the 5′ termini of HCV RNA obtained from HCV replicon cells contains a 5′ monophosphate (17), suggesting that the 5′ terminus of HCV RNA is sensitive to degradation by Xrn-1.…”
Section: Discussionmentioning
confidence: 99%